Potensi Sari Pati Gadung (Dioscorea hispida L.) Sebagai Bioinsektisida Hama Walang Sangit Pada Tanaman Padi (Oryza sativa L.) - Rozi, Zico Fakhrur; Febrianti, Yuli; Telaumbanua, Yardiani (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2018)
Walang sangit (Leptocorisa acuta L.) as a rice bug is a pest that can cause a decrease in rice production (Oryza sativa L.). Excessive use of chemical pesticides will cause resistance or immunity to the pest itself. Gadung (Dioscorea hispida L.) has a compound HCN (cyanide acid) that potentially cause metabolic disturbance in insects. This study aims to determine the extract of gadung tuber effect as bioinsecticide of rice bug against rice. This research was conducted in Biology Laboratory of STKIP PGRI Lubuklinggau South Sumatera Province, with 5 treatment groups and 5 replications. The research design used was complete randomized design (RAL) with P0 control (-) without giving of starch bulb, P1 20 gr / l, P2 40 gr / l, P3 60 gr / l, P4 80 gr / l. Based on the results of analysis with Anava One Path test obtained results Fcount = 7.72 with Ftable = 4.43. It shows there is a significant influence of the extract of gadung tuber as bioinsecticide of rice bug against rice plant.